2020
DOI: 10.1038/s41598-020-71214-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of nocardiosis

Abstract: Nocardia is an opportunistic pathogen that most frequently affects the lungs. Evidence is limited regarding the risk factors for nocardiosis. The current study assessed clinical correlates of nocardiosis. A retrospective study was conducted based on medical records of consecutive adult patients (N = 60) with nocardiosis hospitalized during 2007-2018 at a tertiary hospital in central Israel. A matched comparison group of 120 patients was randomly selected among hospitalized patients with community-acquired pneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 35 publications
(42 reference statements)
1
27
0
1
Order By: Relevance
“…Patients with ICH had a higher risk of nocardiosis due to severe underlying diseases and use of glucocorticoids and/or immunosuppressants. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Patients with ICH had a higher risk of nocardiosis due to severe underlying diseases and use of glucocorticoids and/or immunosuppressants. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Multiple abscesses are seen in approximately half of all cases [30,31], and reach up to 80% among immunocompromised individuals [14]. While recent studies showed that brain imaging is not performed in 20e72% [2,5,6,14,15,24,32] of the patients, CNS nocardiosis can be asymptomatic in up to 43% of the cases [14] and unrecognized CNS involvement may potentially lead to treatment failure. Therefore, it is our opinion that routine contrast-enhanced brain imaging should be performed for all individuals diagnosed with nocardiosis, with the possible exception of immunocompetent patients with primary skin nocardiosis.…”
Section: Clinical Presentation Of Nocardiosismentioning
confidence: 99%
“…The positive association between SOT and nocardiosis was mitigated following adjustment for GC administration in a multivariate model. The association between taking GC and developing nocardiosis was stronger in patients with chronic pulmonary disease (OR: 5.74; 95%CI: 2.75-12.66; P < 0.001) than in the pooled analysis of all nocardiosis cases[ 69 ]. Another analysis on 112 patients with nocardiosis, among which 67 were immunocompromised patients, showed that pulmonary nocardiosis among immunocompromised patients was significantly associated with taking high-dose GC.…”
Section: Side Effectsmentioning
confidence: 99%